Nature and cosmism in the creative heritage of F. M. Dostoevsky (to the 200th anniversary of his birth) - Karako, Petr S. (Journal of the Belarusian State University. Philosophy and Psychology, 2021)
The features of F. M. Dostoevsky views on the natural environment of human life, its conditioning by earthly and cosmic factors are revealed. The religious content of his cosmism is revealed, which, to the greatest extent, is manifested in the substantiation of the essence of the universality of human and human life, the role of Russian Orthodoxy in its implementation. The influence of the writer’s cosmic ideas on the formation of the scientific concept of cosmism by V. I. Vernadsky is emphasised, the general and special in their cosmic views are revealed. The importance of F. M. Dostoevsky’s provisions on the formation of an ethical and aesthetic attitude to nature and its preservation is noted. The conclusion is drawn about his involvement in the literary-artistic and religious-philosophical branches of Russian cosmism.
Keywords: nature; biosphere; Universe; God; Russian Orthodoxy; God-bearing people; universality of life; cosmic manifestation of life; cosmism; Russian cosmism; ethics